Manajemen Supply pada Produk HNI-HPAI Halal Mart di Kabupaten Sambas Perspektif Ekonomi Islam - Oktoviasari, Vera Ayu; Sumar’in, Sumar’in; Awaluddin, Murtiadi (Shar-E : Jurnal Kajian Ekonomi Hukum Syariah, 2024)
Islam is a religion that has a universal system that regulates good business and is in accordance with religion. Many companies are switching to an Islamic business system, called sharia economics. Currently, people really like the Islamic business system. Sharia-based companies include PT HPAI (Herbal Penawar al-Wahida Indonesia), which later became HNI-HPAI (Herba Penawar Al-Wahida Indonesia-Halal Network International). This research aims to determine the supporting and inhibiting factors for implementing supply management at the herbal HPAI halal mart in Sambas Regency. In this research, qualitative research was used. The data collection technique is carried out by means of interviews, then analyzed through data reduction, classifying the data, presenting the data and finally drawing conclusions. The data sources in this research consist of 2, namely primary data and secondary data. One of the supporting factors for carrying out herbal medicine supply management in Sambas Regency can involve operational efficiency, product quality and good marketing strategies. Meanwhile, inhibiting factors may include raw material supply instability, regulatory changes, or logistical constraints. The external supporting factor is that many people know the quality of HPAI products, so they are easy to sell because the prices are affordable. The internal inhibiting factor is not having its own way or rules to handle orders for lots of herbal products by consumers and delays in delivery of goods. These delays are due to an overload of goods to be sent by the expedition.